Design and implementation of a wireless audience response system over a ZigBee network - Fabregas, April Zarah Joy A.; Peña, Mark Laurence O. (2011)
High level of student participation is an essential part of effective learning, and today's trend goes towards implementation of Audience Response System (ARS) in classes to address such factor. This system has been proven to increase audience attentiveness and knowledge retention which are keys to successful student learning. Also, quizzes and recitations are being implemented and graded real-time as students demand transparency in their grades. ARS can solve student passivity in large classes by providing a transparent, real-time and error-free communication service. The goal of the project is to design and implement ARS over ZigBee wireless network. User input handling circuits controlled by the Arduino microcontroller with a ZigBee radio is used to connect users to the central coordinator, Data management is done in the coordinator to show information accurately. These can undertake additional outside processing for different ARS requirements. The project proved successful simulation of ARS application over ZigBee network. Network simulated in large classroom environment had provided 96.11% up to 100% transmission success rates.
Undergraduate student project (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Wireless LANs; Teaching -- Aids and devices; Audience Response System (ARS).; ZigBee